1979
DOI: 10.1021/jf60221a007
|View full text |Cite
|
Sign up to set email alerts
|

Fate of [14C]photoheptachlor in rabbits

Abstract: Tissue distribution, elimination, and metabolism of intraperitoneally administered photoheptachlor was studied in male rabbits. Biological half-life of the compound at 0.8 mg/kg dose level was about 70 days. The radioactivity was excreted almost exclusively in urine. Analyses of the urine extracts revealed that all the radioactivity was in the form of four metabolites, none of which corresponded to the parent compound. Gas chromatography-mass spectrometry analysis of one of the metabolites indicates that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Operation temperatures were as follows: inlet 220 °C, column 190 °C, and detector 220 °C. Purified metabolites were tested for the presence or absence of hydroxyl groups by treatment with Tri-Sil Z (Pierce Chemical Co., Rockford, IL) as described previously (Feroz and Khan, 1979a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Operation temperatures were as follows: inlet 220 °C, column 190 °C, and detector 220 °C. Purified metabolites were tested for the presence or absence of hydroxyl groups by treatment with Tri-Sil Z (Pierce Chemical Co., Rockford, IL) as described previously (Feroz and Khan, 1979a).…”
Section: Methodsmentioning
confidence: 99%
“…to be produced. Khan, 1977b); photoheptachlor in rabbit (Feroz and Khan, 1979b)], information on cts-photochlordane, a possible terminal residue of chlordane, is totally lacking. This report describes the results of excretion, storage, and biotransformations of cis-photochlordane in the rat.…”
mentioning
confidence: 99%
“…The metabolism of intraperitoneally administered 14 C-photoheptachlor was studied in male rabbits by Feroz and Khan (1979). These authors found that radioactivity was excreted almost exclusively in urine.…”
Section: Metabolismmentioning
confidence: 99%
“…However, much higher values were reported for lactating dairy cows (6 to 8 weeks, Bruce et al, 1965;Cook and Wilson, 1971) for pigs (10 to 12 weeks, Raisbeck et al, 1986) and for non lactating cattle (>20 weeks, Raisbeck et al, 1986). Feroz and Khan (1979) reported a half-life value of about 10 weeks for photoheptachlor intraperitoneally administered to rabbits.…”
Section: Excretionmentioning
confidence: 99%
“…Residues of chlordanes and their bioalteration products have been found in fish (Miles and Harris, 1973), pelicans (Blus et al, 1977), and aquatic invertebrates (Bugg et al, 1967;Godsil and Johnson, 1968;Tanita et al, 1976). Chlordanes are refractive to bioalteration in rats (Barnett and Borough, 1974;Brimfield et al, 1978) but more so in freshwater goldfish (Feroz and Khan, 1979a) and cichlid (Feroz and Khan, 1979b). Since cyclodienes are extremely toxic to fish (Tarzwell, 1963;Podowski et al, 1979), the knowledge of their fate (persistence, metabolism, and disposition) and effects on various fish species has been needed for a long time.…”
mentioning
confidence: 99%